A Tool to Identify Key Behaviors and Attributes of High-Performing Nurses. (April 2018) - Cain, Linda B.; Cronin, Sherill Nones; Nelson, Debbie; Meredith, Darla A.; Newman, Karen Profitt; Rudolf, Steven
Abstract : OBJECTIVE: The purpose of this project was to identify key behaviors and attributes that distinguish high-performing nurses to develop a tool for employment screening, staff development, and performance management. BACKGROUND: Selecting nurses who will complement an organization's mission and philosophy is a key step toward achieving quality and safety goals, ensuring patient and family satisfaction, and improving retention rates and overall costs. METHODS: Focus group methodology was used to determine perceptions of high-performing nurses' behaviors and attributes. Content analysis of the meeting transcripts was performed to aggregate data into categories and items. RESULTS: Following several phases of testing with various groups, a 16-item scale has been developed. CONCLUSIONS: This tool has received positive ratings from nurse managers currently using it to interview nurse applicants who best "fit" into the organization's nursing culture. Results will be monitored over time including hiring decisions, preceptor ratings, and retention rates.